Surviving Sources of the Classical Geographers Through Late Antiquity and the Medieval Period - Parroni, Piergiorgio (ARCTIC, 1984)
. The aim in this paper is to follow the evolution of this thread of classical geography from late antiquity through to the mixture of tradition and innovation which succeeded it in the medieval period, without any pretensions to being exhaustive in the naming of authors, and limiting the geographical region discussed to the north. .